(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The Paper Aims: To figure out what are Analysis of problems with Composition, Properties and Biological Activity - Hydrocarbon.By using descriptive method for primary model, synthesis methods and process analysis and analysis of difficulties and discussion, The study of this problem point that, to assess the environmental impact of hydrocarbons on the biosphere, an accurate knowledge of the physical properties and chemical composition of oil and gas. Numerous tragic examples of accidents, such as those associated with a leak hydrogen sulfide gases. Hydrogen sulfide, due to its higher density relative to air settles in the lowlands of the relief, accumulating in calm weather in concentrations up to to lethal. This leads to the death of animals and the death of people. The latter could be avoid by going to elevated windward areas, i.e., knowing the physical properties of this toxic gas.